High-density ‘Spadona’ pear orchard shows reduced tree sensitivity to fire blight damage due to decreased tree vigour - Dafny-Yelin, Mery; Moy, Jehudith Clara; Stern, Raphael A.; Doron, Israel; Silberstein, Miriam; Michaeli, Daphna (Phytopathologia Mediterranea, 2021)
Fire blight, caused by Erwinia amylovora, is a severe disease of pear (Pyrus communis). Highly vigorous trees are more sensitive to E. amylovora damage after summer pruning. Trees grown in high-density orchards have lower vigour than those in low-density orchards, reducing required inputs for pruning and tying, and increasing per hectare yields orchard profitability. Tree damage due to fire blight was assessed in high-density pear orchards vs. the common Israeli low-density orchards. Pear trees were planted at high densities using the spindle system (2500 trees ha-1 for ‘Spadona’ and 1250 trees ha-1 for ‘Coscia’), or at low density (1000 trees ha-1) using palmeta (’Spadona’) or open vase (‘Coscia’) systems. Four years after planting, both orchards were similarly infected with fire blight (11–50 infected blossoms per tree), but 1 year after infection, trees in the high density orchard had blossoms infections in the main limbs or trunk bases compared to the low-density orchard. At 3 years after initial infection, no trees had died in the high density orchard, whereas in the low density ‘Spadona’ orchard, 10% of the trees were wilted. For the more tolerant ‘Coscia’, infection did not progress at either orchard density. These results indicate that in fire blight-susceptible pear cultivars, a high density planting system, associated with reduced tree vigour, presents a decreased risk of fire blight damage.